AN ERROR ANALYSIS ON THE USE OF SIMPLE PAST TENSE AND CONJUNCTION IN WRITING NARRATIVE COMPOSITION (Survey at State SMK in West Jakarta) - Fadilah Fadilah (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2018)
The purpose of this research is to identify the errors of simple past tense and conjunction that is made by students in writing narrative composition. The qualitative method is used by researcher in finishing the research. She took 38 writing of students of state SMK in west Jakarta. The research was held for a month start from June to July. The errors made by students influence the English narrative composition. It can be seen in the writing they made which is showing the sentences they made became meaningless. The learners weren’t used to write or made an English narrative composition by the English teachers so they got some difficulties when they were asked to make an English narrative composition. After having research on the learners’ English narrative composition, the errors happened in simple past tense are 32 mistakes; they are the use of simple past tense 20 mistakes or 30% and the form of simple past tense 12 mistakes or 18%. Conjunction has 20 mistakes or 30% and kinds of errors have 15 mistakes or 22%. Key words: Writing, Error, Simple Past Tense, Conjunctions, Narrative Composition.